Observational Study on How the Frequency of Dialyzer Reuse Impacts Hemodialysis Effectiveness - Ramadi Satryo Wicaksono; Atma Gunawan; Nur Samsu; Achmad Rifai (Indonesian Journal of Kidney and Hypertension, 2024)
Background: The increasing practice of dialyzer reuse in hemodialysis raises critical concerns regarding its impact on efficacy, infection risks, and essential metrics such as Urea Reduction Ratio (URR) and Kt/V values. Addressing these concerns is paramount to establishing safe and optimal reuse limits through comprehensive performance assessments. Objective: To evaluate the feasibility of dialyzer reuse by assessing Kt/V and URR measurements. Methods: A prospective cohort study was conducted at RSUD Dr. Saiful Anwar's Hemodialysis Unit from November 2021 to January 2022. Data collection employed a standardized pilot form designed to collate Kt/V and URR data from all participants. Statistical analyses included repeated measures ANOVA to detect temporal changes in average Kt/V and URR, alongside Spearman correlation analysis to explore variable relationships. Results: The study encompassed 15 participants, revealing a statistically significant decline in both Kt/V and URR values across each reuse group (p < 0.05). Specifically, each subsequent reuse of the dialyzer corresponded to a decrement of 0.0469 units in Kt/V and 1.003 units in URR. Notably, by the 7th reuse, hemodialysis adequacy remained satisfactory, achieving an average Kt/V of 1.61. Furthermore, the study indicated that even up to 11 reuses could achieve a Kt/V > 1.4. Similarly, the average URR value for the 7th reuse was 70.207%, with the potential to maintain URR > 65% even after up to 13 reuses. Conclusion: This study unequivocally affirms that hemodialysis adequacy remains satisfactory up to the 7th reuse of dialyzers, despite observed declines in Kt/V and URR values over successive reuses.